Penerapan Teknologi Budidaya Tanaman Kacang Tanah Di Desa Bone Kancintala Kecamatan Bone Kabupaten Muna - Awaluddin Hamzah; L. Daud Daud; Wade Megawati (Jurnal Ilmiah Penyuluhan dan Pengembangan Masyarakat, 2021)
AbstractThe aim of this research is to analyze technology gain in peanut cultivation. The research was conducted in Bone Kancintala Village, Bone District, Muna Regency. The research location was determined purposively (purposive sampling), with the consideration that most of the people in the village cultivate peanut plants as a source of income. The research sample of 25 peanut farmers was determined using simple random sampling method, namely taking 10% of the total population of 252 heads of families. The results showed that most of the level of application of soil processing technology, use of superior seeds, harvest and post-harvest in peanut cultivation in Bone Kancintala Village were classified as moderate. Meanwhile, most of the application of fertilization technology is still low.